Body, Social and Material Connections as Ways of knowing: A Reflection of the Adult Smoker’s Experiences when learning about and using an Electronic Cigarette - Shari Hrabovsky (Adult Education Research Conference, 2018)
This study explores the body, as a site of learning and the impact of social, and material networks by investigating the lived experiences of adult smokers who use an electronic cigarette device to reduce or quit cigarette smoking.
Keywords: Embodied Learning; Actor Network Theory; Electronic Cigarette; Adult Education